2020
DOI: 10.1101/2020.03.05.973271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An active chromatin interactome in relevant cell lines elucidates biological mechanisms at genetic risk loci for dermatological traits

Abstract: In the last 15 years Genome wide association studies (GWAS) have uncovered the genetic factors that contribute to disease risk for many disorders, yet the biological significance of many of these associations remain unclear. This is because about 90% of these variants are predicted to affect regulatory elements that are highly cell-type specific and can affect distal genes through chromatin interaction mechanisms and, therefore, understanding their role in disease is challenging.Previous studies have attempted… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…The combination of the different techniques described above has led to the identification of relevant genes in autoimmune diseases. As an example, recent studies combining publicly available Hi-C, CHi-C and HiChIP data identified novel candidate genes for SSc and PsA [ 86 ].…”
Section: Epigenomics Studiesmentioning
confidence: 99%
“…The combination of the different techniques described above has led to the identification of relevant genes in autoimmune diseases. As an example, recent studies combining publicly available Hi-C, CHi-C and HiChIP data identified novel candidate genes for SSc and PsA [ 86 ].…”
Section: Epigenomics Studiesmentioning
confidence: 99%